Beginning Silverlight 2 - Lair, Robert (Springer, 2017)
With the need for a richer user experience ever more in focus when creating web applications, Microsoft has released Silverlight, the new cross–browser, cross–platform plug–in that allows developers to create rich interactive applications for the Web.